2022
DOI: 10.1177/03063070221105308
|View full text |Cite
|
Sign up to set email alerts
|

Keep the fire burning: Social entrepreneurs’ motives, role stress, perceived work competence and passion

Abstract: This study examines factors affecting social entrepreneurs’ passion, focusing on their motives, job stress, and perceived work competence. The analysis of the survey data of 264 self-identified social entrepreneurs working in different types of organizations reveals that other-oriented motives are strongly associated with passion while self-oriented motives are not. The results also show that job stress is negatively correlated with social entrepreneurs’ passion. When the perceived work competence is included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Social entrepreneurs have also found that other-oriented motives are significantly related to their work, while self-oriented motives are not. Furthermore, the level of perceived work competence mediates the relationship between enthusiasm and job stress, indicating that high levels of work competence can benefit social entrepreneurs' enthusiasm and can strengthen the association between enthusiasm and other-centered goals [106].…”
Section: Entrepreneurial Mindset (Em) and Entrepreneurial Motives (Em...mentioning
confidence: 98%
See 1 more Smart Citation
“…Social entrepreneurs have also found that other-oriented motives are significantly related to their work, while self-oriented motives are not. Furthermore, the level of perceived work competence mediates the relationship between enthusiasm and job stress, indicating that high levels of work competence can benefit social entrepreneurs' enthusiasm and can strengthen the association between enthusiasm and other-centered goals [106].…”
Section: Entrepreneurial Mindset (Em) and Entrepreneurial Motives (Em...mentioning
confidence: 98%
“…Overall, EM and EMTs play significant mediating roles in the relationship between ECs and EI, as evidenced by previous research [61,64,88,103,104]. However, there is a lack of integrated research on the role of EM and EMTs in driving EI [99][100][101]105,106]. Based on this deficiency, we formulated the following hypotheses:…”
Section: Entrepreneurial Mindset (Em) and Entrepreneurial Motives (Em...mentioning
confidence: 99%